Die Moschee von Ramazan Efendi in Ayntab: Eine Annäherung an die Architekturgeschichte der Stadt - Tupev, Mustafa (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2024)
This article aims to present and discuss the architecture of the mosque of Ramazan Efendi in Ayntab (today Gaziantep in southern Turkey). Based on the physical appearance of the dated monument (1672), conclusions are drawn about formal developments, continuities, and innovations within the city borders. From the perspective of function, building typology, and structural elements, the mosque of Ramazan Efendi can be considered representative of an identifiable group of buildings with similar features within Ayntab. These structures have a rectangular sanctuary consisting of two naves running parallel to the qibla and an open porch. The main entrance to the sanctuary and the mihrab serve as an axis of symmetry; the naves have the same height. The sanctuary is covered with cross vaults, the arches of which rest on square piers. A variation of this scheme is mosques with a domed mihrab-area. [...]